Pertanggungjawaban Sosial Universitas: Implementasi Model Cycle Relations - Lina Sinatra Wijaya; Krismiyati Krismiyati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2016)
The competition among Higher Education is getting tougher. They need to do their best in order to maintain their existence and getting more students coming to their institutions. One way to achieve that goal is through carrying out Corporate Social Responsibility (CSR) programs or University Social Responsibility (USR) for university. This study tries to investigate the implementation of ‘Cycle Relations’ model in CSR to increase the intake of Higher Education. This study involved seven Higher Educations and nineteen High schools in Central Java. In collecting the data, it used a depth-interview method with all the related parties in this study. The result showed that most of the Higher Education institutions have implemented Corporate Social Responsibility program in various ways. Their target audience included the high schools, society, and parents. From the model implementation, it showed that the CSR program did have an impact towards the intake in their institution. However, one important thing to consider is that the role of the teachers at schools was quite significant in influencing the students to choose which university to go. This reflects that although the Higher Education institution have planned and carried out CSR programs according to what the target audiences’ need, it does not guarantee that it will have direct impact towards their intake because the influence of teacher is quite significant. It may have a bigger impact in long term as the target audiences know the quality and contribution of the Higher Education institutions.